Urban forest: Buildings that capture and utilise carbon dioxide - Wikestad, Martin (My University, 2025)
The built environment is a major contributor to the global CO₂ emissions (United Nations Environment Programme, 2023), making it essential for us to explore new ways of designing our built environment in a way that not only reduces its emissions but also actively participates in the reduction of greenhouse gases in our atmosphere. This thesis investigates the potential of buildings to function as carbon sinks by integrating Carbon Capture into architectural design. By treating facades as active components in carbon sequestration, the study envisions buildings as part of an “urban forest” that removes CO₂ from the atmosphere, much like trees in a natural ecosystem. The thesis builds upon existing carbon capture technologies, developed by Dr Klaus Lackner (2009) at Columbia University, and explores their potential architectural integration through a design-driven case study where filters serve a dual purpose of offering shade to reduce solar heat gain while simultaneously capturing CO₂. In an effort to address one of the major challenges of carbon capture, what to do with the captured CO₂, this thesis also explores, beyond sequestration, how the captured CO₂ can be repurposed within the building itself, creating a closed-loop system. The thesis uses data from non building devices to calculate the magnitude and possibility of integrating carbon capture on a buildings facade. Drawing on data from Lackner (2009), this thesis develops a design proposal located on a site in Gothenburg showing that the building’s closed-loop system can sequester and reuse more CO₂ than is emitted during its construction. With this thesis design and in the given context, the proposed design could capture and utilize approximately 200 tonnes of CO₂ annually.
Keywords: Carbon capture, climate-positive architecture, regenerative design, built environment, CO₂ sequestration